PARTY LIFE IN THE KINGDOM OF SERBIA AT THE END OF THE 1902. AND THE BEGINING OF 1903. - Pešić, Miroslav D (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
After the resignation of the Government of Pero Velimirović, the cabinet of General Dimitrije Cicnarmarković was formed on November 19, 1902. King Alexander dissolved the Assembly elected during the mandate of the Government of Mihailo Vujić. The formation of this government was a sign that the last Obrenović wanted to return to personal rule, as he did in 1894. The opposition quickly saw the king’s plans to change the Constitution, and because of that, it sharply attacked him through the press. The fierce opposition to Cincarmarković’s Government consisted of: liberals gathered around Jovan Avakumović, independents and old radicals gathered around Nikola Pašić and Mihailo Vujić. On April 6, 1903, King Alexander repealed the 1901 Constitution. The proclamation that followed after 45 minutes restored the Constitution from 1901. The National Assembly was dissolved by the first and second acts, while the elections for the National Assembly and the Senate were scheduled for June 1, 1903. The re-establishment of the personal regime accelerated the preparations of the conspirators who carried out a coup on the night between June 10 and 11, 1903.